Preferential secretion of inducible HSP70 by vitiligo melanocytes under stress. (13th January 2014) - Mosenson, Jeffrey A.; Flood, Kelsey; Klarquist, Jared; Eby, Jonathan M.; Koshoffer, Amy; Boissy, Raymond E.; Overbeck, Andreas; Tung, Rebecca C.; Le Poole, I. Caroline
Summary Inducible HSP70 (HSP70i) chaperones peptides from stressed cells, protecting them from apoptosis. Upon extracellular release, HSP70i serves an adjuvant function, enhancing immune responses to bound peptides. We questioned whether HSP70i differentially protects control and vitiligo melanocytes from stress and subsequent immune responses. We compared expression of HSP70i in skin samples, evaluated the viability of primary vitiligo and control melanocytes exposed to bleaching phenols, and measured secreted HSP70i. We determined whether HSP70i traffics to melanosomes to contact immunogenic proteins by cell fractionation, western blotting, electron microscopy, and confocal microscopy. Viability of vitiligo and control melanocytes was equally affected under stress. However, vitiligo melanocytes secreted increased amounts of HSP70i in response to MBEH, corroborating with aberrant HSP70i expression in patient skin. Intracellular HSP70i colocalized with melanosomes, and more so in response to MBEH in vitiligo melanocytes. Thus, whereas either agent is cytotoxic to melanocytes, MBEH preferentially induces immune responses to melanocytes.